Strategi Marketing Mix dalam Pengembangan Usaha Berdasarkan Analisis Product Life Cycle (PLC): Studi pada Usaha Maharaja Garment Bangkalan - Ema Oktavia Rahmawati; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Every business has a goal to achieve profitability and when the business is successful, further development becomes a necessity. Today, the business that continues to grow and is always sought after by people is the convection business. This convection business aims to meet the needs of clothing as people's main clothing by placing orders in large quantities and following the development of trends. An example is the